Regulation of Plant Growth, Photosynthesis, Antioxidation and Osmosis by an Arbuscular Mycorrhizal Fungus in Watermelon Seedlings under Well-Watered and Drought Conditions - Mo, Yanling; Wang, Yongqi; Yang, Ruiping; Zheng, Junxian; Liu, Changming; Li, Hao; Ma, Jianxiang; Zhang, Yong; Wei, Chunhua; Zhang, Xian (Frontiers in Plant Science, 2016)
Drought stress has become an increasingly serious environmental issue that influences the growth and production of watermelon. Previous studies found that arbuscular mycorrhizal (AM) colonization improved the fruit yield and water use efﬁciency of watermelon grown under water stress; however, the exact mechanisms remain unknown. In this study, the effects of Glomus versiforme symbiosis on the growth, physio-biochemical attributes, and stress-responsive gene expressions of watermelon seedlings grown under well-watered and drought conditions were investigated. The results showed that AM colonization did not significantly influence the shoot growth of watermelon seedlings under well-watered conditions but did promote root development irrespective of water treatment. Drought stress decreased the leaf relative water content and chlorophyll concentration, but to a lesser extent in the AM plants. Compared with the non-mycorrhizal seedlings, mycorrhizal plants had higher non-photochemical quenching values, which reduced the chloroplast ultrastructural damage in the mesophyll cells and thus maintained higher photosynthetic efficiency. Moreover, AM inoculation led to signiﬁcant enhancements in the enzyme activities and gene expressions of SOD, CAT, APX, GR and MDHAR in watermelon leaves upon drought imposition. Consequently, AM plants exhibited lower accumulation of MDA, H2O2 and O2- compared with non-mycorrhizal plants. Under drought stress, the soluble sugar and proline contents were significantly increased, and further enhancements were observed by pre-treating the drought-stressed plants with AM. Taken together, our findings indicate that mycorrhizal colonization enhances watermelon drought tolerance through a stronger root system, greater protection of photosynthetic apparatus, a more efﬁcient antioxidant system and improved osmoregulation. This study contributes to advances in the knowledge of AM-induced drought tolerance.